Driving factors of community-level leaf stoichiometry patterns in a typical temperate mountain meadow ecosystem of northern China - Zhang, Xiaolong; Qin, Hao; Zhang, Yinbo; Niu, Junjie; Wang, Yongji; Shi, Lijiang (Frontiers in Plant Science, 2023)
In ecological stoichiometry, the stoichiometry and spatial distribution of leaf carbon, nitrogen, and phosphorus are important research topics. Various studies have assessed leaf stoichiometry and its relationships with environmental factors at different scales. However, how the leaf carbon, nitrogen and phosphorus stoichiometric characteristics of the same vegetation type at the community level vary with environmental factors along a continuous altitudinal gradient remains poorly understood. In this paper, 13 sampling sites along an altitudinal gradient of 1800—3011 m in a typical temperate mountain meadow ecosystem on the southern slope of the Wutai Mountain in North China were sampled to explore the response of leaf carbon, nitrogen and phosphorus stoichiometric characteristics to altitude change, and then quantified the contribution of driving factors. We found that the community-level leaf stoichiometry of mountain meadows differed significantly at different altitudes, and an increase in altitude significantly decreased community-level leaf total nitrogen (LTN) and leaf total phosphorus (LTP); however, the leaf total carbon (LTC), C∶N, C∶P, and N∶P increased with an increase in altitude. Additionally, with increasing altitude, soil properties showed significant trends. Soil organic carbon (SOC), soil total nitrogen (STN) soil total phosphorus (STP), soil water content and soil electrical conductivity increased significantly, but soil temperature, soil bulk density and soil pH exhibited the opposite trend. Our results suggested that altitude, soil electrical conductivity and soil bulk density significantly influenced the changes in the leaf stoichiometric characteristics, explaining 75.5% of the total variation, and altitude had the greatest influence (36.6%). In the temperate mountains, altitude played a decisive role in affecting patterns of meadow plant nutrients and stoichiometry and was more important than soil in explaining leaf C∶N∶P stoichiometry variations. Our findings provide important references to understand the responses of plant stoichiometry to altitudinal gradients.